Global, regional, and national burdens of non-alcoholic fatty liver disease attributable to smoking from 1990 to 2021 - Pengyue Zhang; Jie Zhu; Xinlei Chen; Chunhui Tao; Jianmei Zhou; Zhenhua Zhang; Xiaodan Hong (Ecotoxicology and Environmental Safety)
Background: Tobacco is a major environmental pollutant, and smoking is a recognized risk factor for non-alcoholic fatty liver disease (NAFLD). However, the global epidemiological burden of smoking-related NAFLD remains unclear. This study aimed to quantify the burden of NAFLD attributable to smoking from 1990 to 2021, focusing on disability-adjusted life years (DALYs), mortality rates, and temporal trends. Methods: Data were extracted from the Global Burden of Disease Study 2021 and analyzed at global, regional, and national levels. Age, sex, region, and socio-demographic index (SDI) were included. Key measures included age-standardized DALY rates (ASDR), age-standardized mortality rates (ASMR), and average annual percentage changes (AAPCs). Trends were further stratified by age, sex, and SDI. Results: Globally, the ASMR of NAFLD attributable to smoking demonstrated a upward trend (AAPCASMR=0.27[95 % CI, 0.17–0.37], P < 0.001). The most substantial increases from 1990 to 2021 were observed in Australasia and Southern Latin America. The AAPC for ASDR was 2.89[95 %CI, 2.5–3.29] and 2.84[95 %CI, 2.16–3.52], respectively. The burden was significantly higher in males, with DALY rates rising with age and peaking at 65–69 years (8.84/100,000; 95 % UI: 2.77–15.69). An inverse U-shaped association between SDI and disease burden was noted. Join-point analysis revealed increasing trends in low-medium SDI regions and among females in high-SDI regions. Conclusion: Despite declining smoking prevalence, the burden of smoking-related NAFLD continues to rise, especially in low-middle income regions and high-income females. Strengthened tobacco control and targeted NAFLD prevention strategies are urgently needed.